Images from memory: affective experiences of a teacher/artist (Palíndromo, 2023)
The text presents an excerpt from my doctoral thesis in which I tell through poetic essays my aesthetic and sensitive experiences that affected my teaching practice as a photography teacher and as a visual artist in the use of photography. The thesis, defended in the midst of the pandemic in 2020, used the cartography method and the data collection made use of photographs published in a personal profile on the social media Instagram in the form of a file/diary. This profile, created at the beginning of the doctorate, initially had the objective of recording the day-to-day of the doctoral process. However, it ended up becoming an archive of my gaze during the four years. Through it I stored images that moved me or reminded me of a distant past that was present at all times. Thus, as an itinerant flâneur, I sailed through the waters of memory, marked by a delicate look that takes effect through photography, bringing the affections that crossed/cross and constituted/constitute my subjectivity. Through the images I create narratives and at this moment, I present some stories, notions and concepts that guided the investigation.
Keywords: Image; Memory; Experience; Teacher/artist; Photography